Chemical Synthesis, Characterisation, and Biocompatibility of Nanometre Scale Porous Anodic Aluminium Oxide Membranes for Use as a Cell Culture Substrate for the Vero Cell Line: A Preliminary Study - Poinern, G.; Le, X.; O'Dea, M.; Becker, Thomas; Fawcett, D. (Hindawi Publishing Corporation, 2014)
In this preliminary study we investigate for the first time the biomedical potential of using porous anodic aluminium oxide (AAO) membranes as a cell substrate for culturing the Cercopithecus aethiops (African green monkey) Kidney (Vero) epithelial cell line. One advantage of using the inorganic AAO membrane is the presence of nanometre scale pore channels that allow the exchangeof molecules and nutrients across the membrane. The size of the pore channels can be preselected by adjusting the controlling parameters of a temperature controlled two-step anodization process. The cellular interaction and response of theVero cell linewith an in-house synthesisedAAOmembrane, a commercially availablemembrane, and a glass controlwere assessed by investigating celladhesion, morphology, and proliferation over a 72 h period.The number of viable cells proliferating over the respective membrane surfaces revealed that the locally produced in-house AAO membrane had cells numbers similar to the glass control. The study revealed evidence of focal adhesion sites over the surface of the nanoporous membranes and the penetration of cellular extensions into the pore structure as well. The outcome of the study has revealed that nanometre scale porous AAO membranes have the potential to become practical cell culture scaffold substrates with the capability to enhance adhesion and proliferation of Vero cells.